2018
DOI: 10.1038/s41598-018-31167-1
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Manipulation of the APC-β-Catenin Pathway During Peripheral Neuron Regeneration

Abstract: Molecules and pathways that suppress growth are expressed in postmitotic neurons, a potential advantage in mature neural networks, but a liability during regeneration. In this work, we probed the APC (adenomatous polyposis coli)-β-catenin partner pathway in adult peripheral sensory neurons during regeneration. APC had robust expression in the cytoplasm and perinuclear region of adult DRG sensory neurons both before and after axotomy injury. β-catenin was expressed in neuronal nuclei, neuronal cytoplasm and als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 50 publications
(73 reference statements)
0
22
0
Order By: Relevance
“…We showed that after sciatic nerve injury IB4 expression is found not only in small pain neurons but also in medium-sized neurons. IB4 is believed to be a marker of small nociceptive neurons that have unmyelinated processes in the sciatic nerve innervating the epidermis and showing lower survival both in vitro and in vivo (56). Therefore, this type of neurons is more prone to cell death as compared to medium and large diameter neurons, which is consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that after sciatic nerve injury IB4 expression is found not only in small pain neurons but also in medium-sized neurons. IB4 is believed to be a marker of small nociceptive neurons that have unmyelinated processes in the sciatic nerve innervating the epidermis and showing lower survival both in vitro and in vivo (56). Therefore, this type of neurons is more prone to cell death as compared to medium and large diameter neurons, which is consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Quantification of bands was through Adobe Photoshop and the band densities were normalized with those of the loading control. The approach for Western immunoblots has been previously published in work from our laboratory (Duraikannu et al, 2018).…”
Section: Western Immunoblotsmentioning
confidence: 99%
“…MUPs may stimulate olfactory cells, namely vomeronasal epithelial receptors either directly or through their binding to volatile hydrocarbons. They are approximately 18-20 kDA sized protein members of the lipocalin family with eight antiparallel β-strands organized in a β barrel with additional α helices, forming a pocket that sequesters organic molecules for later release as an olfactory stimulant, mainly for avoidance by males and attraction by females (Beynon & Hurst, 2003;Gomez-Baena et al, 2014;Kwak et al, 2012;Schiefner & Skerra, 2015). We encountered unexpected patterns of MUP expression in peripheral sensory neurons of outbred laboratory mice leading, in turn, to its further unforeseen appearance, described here, in dermal hindpaw footpad sweat glands.…”
Section: Introductionmentioning
confidence: 99%
“…In sensory neurons, knockdown of APC increased β-catenin nuclear accumulation, was associated with upregulation TCF and lymphoid enhancing binding factor (LEF) transcription factors (Figure 4). In addition, knockdown of APC in adult DRG neurons increased neurite outgrowth of both uninjured and preconditioned neurons (Duraikannu et al, 2018). Narciso et al (2009), showed that β-catenin expression increased in Galectin-3 knockout mice associated with enhanced neuronal survival and axon regeneration after traumatic nerve lesions.…”
Section: Apc and Its β-Catenin Partnermentioning
confidence: 99%
“…Furthermore, interactions between β-catenin and TCF3 were required for SC myelination in vivo (Tawk et al, 2011). Inhibition of β-catenin and TCF activity impaired neurite outgrowth in DRG neurons in vitro (Duraikannu et al, 2018). In vivo , local knockdown of APC following nerve trunk crush injury using siRNA increased the repopulation of myelinated axons and was associated with improved indices of functional recovery.…”
Section: Apc and Its β-Catenin Partnermentioning
confidence: 99%